Self-gelling bioink with loaded growth factor for regeneration of subcutaneous tissues. (2022) - Ullah, Faheem; Javed, Fatima; Abdul Hamid, Zuratul Ain
Abstract: Advanced wound healing need specific skin tissue engineering which is only possible by combining various medications and bioactive materials in an engineered microstructure of imprinted product. The current study aims to develop printable bioink with controlled gelling, rheological, physicochemical and thermomechanical properties with added growth factor for tissue regeneration by using 3-D Bioprinting technology. The study introduces self-gelling hydrogel based bioink of chitosan co-poly(methylmethacrylic-acid, (CS- co -PMMA) via Freee radical copolymerization. The bioink in term of self-gelling ability, physicochemical and electrokinetic properties were characterized by using zeta nanosizer and laser light scattering respectively. The predominant rate of gelation was attributed to the stronger Hydrogen-bonding and electrostatic interactions between cationic CS and anionic PMMA pendant groups. The imprinted bioink presented a higher survival rate of 92 % in comparison to 67 % reported survival rate for pure chitosan- built bioink. The imprinted bioink showed maximum stability (zeta potential (z.p≈ 32 mV) at physiological pH. The histological assay of the imprinted bioink with added growth factor (Nicotinamide) showed a clear healing clue for the infected subcutaneous tissue. The results revealed that the imprinted bioink could be potentially used in 3-D Bioprinting for subcutaneous tissue regeneration.